The 5 stakeholders in a business / Yonina Sikim - Sikim, Yonina (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
Customers are a company's lifeblood. They are the ones who purchase the company's goods or services. Customers' requirements and desires are continuously changing, thus firms must be ready to adapt in order to remain successful. Creditors are often overlooked as stakeholders in a business, but they play a vital role in its success. They are the people or organizations who have loaned money to the business and are therefore owed repayment. Creditors have a vested interest in the success of the business because if the business fails, they may not be repaid their loans.